Electro‐kinetic Separation of Rare Earth Elements Using a Redox‐Active Ligand. (22nd September 2017) - Fang, Huayi; Cole, Bren E.; Qiao, Yusen; Bogart, Justin A.; Cheisson, Thibault; Manor, Brian C.; Carroll, Patrick J.; Schelter, Eric J.
Abstract: Purification of rare earth elements is challenging due to their chemical similarities. All of the deployed separation methods rely on thermodynamic properties, such as distribution equilibria in solvent extraction. Rare‐earth‐metal separations based on kinetic differences have not been examined. Herein, we demonstrate a new approach for rare‐earth‐element separations by exploiting differences in the oxidation rates within a series of rare earth compounds containing the redox‐active ligand [{2‐( t BuN(O))C6 H4 CH2 }3 N] 3− . Using this method, a single‐step separation factor up to 261 was obtained for the separation of a 50:50 yttrium–lutetium mixture.